PERANCANGAN SISTEM INFORMASI INVENTORI ASET SARANA PERLENGKAPAN SEKOLAH DI SEKOLAH SMPIT PUTRA CENDEKIA DEPOK BERBASIS WEB - Agung Nugraha; Ahmad Fauzi; Andi Dwi Pangestu (Jurnal Riset Teknik Komputer, 2024)
Asset data management at SMPIT Putra Cendekia is currently still being done manually. Recording and storage is written in long books, and data is stored in archive form, so there is a high possibility of loss of archive books, exposure to rain, burns, and others. The amount of data that is large and not fixed makes the administration and operators take a long time to find archived data if at any time the archive data wants to be used. Therefore, an information system for managing school asset data is needed, so as to facilitate the administration and operators in managing accurate data and data collection. In this study, researchers used one type of qualitative method, namely the grounded theory method by collecting data through interviews, observation, and documentation. This application is made using React JS as Front-end and PHP with XAMPP as Back-end in making RestAPI. To facilitate work in the form of input, expenditure, and reporting as well as to prevent errors that often occur today.